Sikap Bahasa Guru TK di Kecamatan Pattallassang Kabupaten Takalar Terhadap Penggunaan Bahasa Ibu - St. Nurhadijah Akhmad; Andi Agussalim Aj; Sultan Sultan (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstrak. This study aims to describe the language attitudes of Kindergarten teachers towards the use of their mother tongue. To find out, researchers used three components of language attitudes, namely: conative components, affective components and cognitive components. This type of research is descriptive quantitative research. The focus of the research refers to the language attitude of the Kemala Bhayangkari Kindergarten teachers in Kec. Pattallasang Kab. Takalar. The research subject is Kemala Bhayangkari Kindergarten teacher consisting of 15 people. The research instrument is a questionnaire. The questionnaire used on the Likert scale in the form of a check consists of 20 items. The data collection technique used is a questionnaire, the type of questionnaire used in this study is a closed question. Based on the results of the research data, the percentage of the cognitive component of the Kindergarten teacher towards the use of the mother tongue is in the positive category seen from the percentage consisting of 7 statement items. In the data, the percentage of the affective component consists of 8 statement items indicating that they are in the positive category. In the data, the percentage of the conative component of the Kindergarten teacher towards the use of the mother tongue is in the positive category seen from the percentage consisting of 5 statement items. Keywords: Language Attitude, Language Attitude Components, Kindergarten Teachers, Mother Language